Chemical constituents of Dracocephalum nutans (International Journal of Biology and Chemistry, 2015)
In this study we investigate the chemical constituent in aerial parts of Dracocephalum nutans. The moisture content (6.13%), total ash (2.18%), extractives (35.25%) and quantitative and qualitativeanalysis of biologically active constituents of aerial parts of Dracocephalum nutans were determined. In The Institute of Combustion Problems using the method of multi–element atomic emission spectralanalysis in the ash of Dracocephalum nutans were found 11 macro–micro elements, main of them was K(794.5750 μg/ml), Ca (440.63 μg/ml), Fe (4.5005 μg/ml), Zn (1.6911 μg/ml). The volatile oil constituteswere extracted from the aerial parts of Dracocephalum nutans by water steam distillation were analyzed by GC–MS method. More than forty compounds were separated. Their relative contents were determinedby area normalization in which 45volatiles were identified. The major volatile oils of 1H–Cycloprop[e] azulen – 7 – ol, decahydro – 1, 1, 7 – trimethyl – 4 – methylene – (14.23%), Caryophyllene oxide (11.30%),1, 6 – Octadien – 3 – ol, 3, 7 – dimethyl – (7.69%), (–) – myrtenyl acetate (5.67%), Naphthalene, 1, 2, 3, 4, 4A, 5, 6, 8A – octahydro – 7 – methyl – 4 – methylene (5.29%), (–) – spathulenol (4.76%), Benzene, 1 – methoxy – 4 – (1 – propenyl) – (4.73%), 4 ah – cycloprop [e]azulen – 4A – ol, decahydro – 1, 1, 4, 7 – tetra – [ethenyl] – (4.65%), Germacrene D (4.42%), (E) – 3(10) – caren – 4 – ol (4.23%), Bicyclo [7.2.0] undec – 4 – ene, 4, 11, 11 – trimethyl – 8 – methulene – (3.67%), α –Caryophyllene (3.60%), 12 – oxabicyclo [9.1.0] dodeca – 3, 7 – diene, 1, 5, 5, 8 – tetramethyl (2.13%).